2002
DOI: 10.1159/000068590
|View full text |Cite
|
Sign up to set email alerts
|

Violent Women, Blame Attribution, Crime, and Personality

Abstract: Background: The attribution of blame for criminal act has an impact, both on the way the offender must come to terms with the offence and on the risk of recidivism. Blame attribution has been found to be related to the type of crime and personality. Aims: This study examined the relationship of blame attribution and feelings of guilt in violent female offenders, according to factors related to crime, background and personality. Methods: The Gudjonsson Blame Attribution Inventory (BAI) and the Defense Style Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 42 publications
(55 reference statements)
3
15
0
2
Order By: Relevance
“…These findings resemble results from previous studies on the relationship between victims and psychopathic male and female offenders (H€ akk€ anen-Nyholm & Hare, 2009;Weizmann-Henelius, Sailas, Viemer€ o, & Eronen, 2002;Williamson et al, 1987), although only the Weizmann-Henelius et al (2002) study comprised a sample of violent female offenders. In general, it has been found that violence by women is more often displayed within family spheres, for example, in intimate partner violence, child abuse, or violence towards other family members (Robbins et al, 2003).…”
supporting
confidence: 85%
“…These findings resemble results from previous studies on the relationship between victims and psychopathic male and female offenders (H€ akk€ anen-Nyholm & Hare, 2009;Weizmann-Henelius, Sailas, Viemer€ o, & Eronen, 2002;Williamson et al, 1987), although only the Weizmann-Henelius et al (2002) study comprised a sample of violent female offenders. In general, it has been found that violence by women is more often displayed within family spheres, for example, in intimate partner violence, child abuse, or violence towards other family members (Robbins et al, 2003).…”
supporting
confidence: 85%
“…Studies of blame judgments in psychopaths are difficult to come by and, like most studies involving psychopathy, composed of a small number of participants. For one study on blame attributions in female psychopaths (Weizmann-Henelius, Sailas, Viemerö, and Eronen 2002). 10.…”
Section: Resultsmentioning
confidence: 99%
“…To determine if SDR would be a mechanism in the different validities of the CRAI and PCRAI, partial correlations were performed between the personal instructional sets (PCRAI) and the BAI controlling for SDR (Self‐deception enhancement 1 ). The strategy for this analysis was as follows: first, the BAI, an established and well‐published instrument, was considered to be the valid standard for criminal attributions (Dolan, 1995; Weizmann‐Henelius, Sailas, Viemerö, & Eronen, 2002). Second, discrepant pairs of CRAI and PCRAI correlations with the BAI were identified from Table 1.…”
Section: Resultsmentioning
confidence: 99%